2023
DOI: 10.26717/bjstr.2023.50.007960
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa: A Source of Antiparasitic Compounds?

Abstract: Cannabis sativa (hemp, marijuana, ganja) is a plant with industrial, medicinal, and recreational uses that synthesizes phytocannabinoids, a group of compounds from which tetrahydrocannabinol (THC) and cannabidiol (CBD) outstand by their known high and low psychoactive properties. These and other cannabinoids (endocannabinoids and synthetic derivatives with modulating effects over cannabinoid receptors CB1/2) have been tested in vitro using cultured parasites and in vivo in rodent models of protozoosis affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…It is used for the treatment of different pathologies, such as inflammatory and neurodegenerative diseases, epilepsy, multiple sclerosis, arthritis, schizophrenia and cancer [ 34 ]. Moreover, very recently the potential use of CBD against parasitic infection has been highlighted [ 35 ]. It has been reported that treatment with CBD (30 mg/kg for 7 days) in a murine model of cerebral infection with Plasmodium berghei, caused lower parasite load in the brain and prevented memory deficits and anxiety behavior leading to a higher survival rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is used for the treatment of different pathologies, such as inflammatory and neurodegenerative diseases, epilepsy, multiple sclerosis, arthritis, schizophrenia and cancer [ 34 ]. Moreover, very recently the potential use of CBD against parasitic infection has been highlighted [ 35 ]. It has been reported that treatment with CBD (30 mg/kg for 7 days) in a murine model of cerebral infection with Plasmodium berghei, caused lower parasite load in the brain and prevented memory deficits and anxiety behavior leading to a higher survival rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%